Media Learning Aqidah Through The Tadaruziah Waqi’Iah Approach For Elementary School Students In Bandung - Muhamad Parhan; Usup Romli; Mohammad Rindu Fajar Islamy; Salima Muhammad Husein (Didaktika Religia, 2021)
This research aims to develop Islamic Education learning media for the material of faith in elementary schools (SD). The basis for developing learning media results from previous research found many teachers' tendency to experience difficulties in using media in Islamic Islamic education learning material in elementary schools. Therefore, this research is significant to obtain an appropriate learning media formula in providing a complete understanding of the subject matter of faith in elementary school students. The research method used in this research is research and development (R & D) with the compilation of Islamic Islamic Studies learning media in elementary schools (SD), which delivers an understanding of Islamic Islamic education in faith material to get references and ease in learning. Students can also understand the material of faith efficiently and effectively through the tadaruziah waqi'iah approaches.